Pemberdayaan Masyarakat Melalui Manager Komunitas sebagai Upaya Peningkatan Kesehatan Ibu dan Anak - Sunarsih, Tri; Shanti, Elvika Fit Ari (Jurnal Pengabdian Dharma Bakti, 2019)
The Maternal and Child Health Program (MCH) is one of the priorities of the Ministry of Health and a key indicator in the National Long Term Development Plan (RPJPN) 2005-2025.Â The high maternal mortality (MMR) in Indonesia to make the Government put efforts decrease AKI as a program priority. The clinic gamping is a health center with the highest number of infant deaths, each of which is 6 babies. The highest cause of infant mortality is low birth weight (Dinkes Sleman, 2016). The location of Ambarketawang Village which be used as a place for KKN-PPM is the clinik Gamping area. The number of productive population in Ambarketawang Village occupies a majority position (age between 20-45 years), thus requiring more attention to reproductive health as an effort to reduce MMR and IMR (Profile of Ambarketawang Village, 2014). In overcoming these problems, real and realistic efforts are needed by involving the active role of the community by utilizing the potential of local organizations because their activities reach the operational level carried out by health cadres. But based on observations in the field the level of education of the average cadre is low. Many health cadres still do not understand about the MCH program, skills and abilities in managing activities are still limited, cadres still lack understanding about their duties as Village Facilitators. In addition, community participation is still limited to the phase of just being involved and being part of the activity. The Midwifery Study Program is one of the technical implementing units in the field of health education. The basic thinking of this level of education is to help the government suppress the high MMR and IMR in Indonesia. Therefore KKN activities part of the midwifery education process must be done to provide students with the ability to provide community midwifery care that is oriented towards community empowerment. The method in this KKN-PPM activity will be carried out in two activities, namely: First, debriefing the Gamping Tengah village community through the formation of community managers consisting of elements of health cadres and community leaders. Second, mentoring community empowerment practices carried out by community managers in families in the field of MCH. In accordance with the problems raised earlier, the objectives to be achieved in this activities are: forming community managers as village facilitators, developing community managers who have an understanding of the concept of maternal and child health programs, forming baby food cafe programs, forming healthy youth groups as maternal health preparation, making OCOC (one cadre one client) program for pregnant women.Keyword: community manager, Maternal and Child Health